Cytotoxic Effects of Hellebrigenin and Arenobufagin Against Human Breast Cancer Cells - Zhang, Yu; Yuan, Bo; Bian, Baolin; Zhao, Haiyu; Kiyomi, Anna; Hayashi, Hideki; Iwatani, Yui; Sugiura, Munetoshi; Takagi, Norio (Frontiers in Oncology, 2021)
Development of new therapeutic strategies for breast cancer is urgently needed due to the sustained emergence of drug resistance, tumor recurrence and metastasis. To gain a novel insight into therapeutic approaches to fight against breast cancer, the cytocidal effects of hellebrigenin (Helle) and arenobufagin (Areno) were investigated in human estrogen receptor (ER)-positive breast cancer cell line MCF-7 and triple-negative breast cancer cell line MDA-MB-231. Helle exhibited more potent cytotoxicity than Areno in both cancer cells, and MCF-7 cells were more susceptible to both drugs in comparison with MDA-MB-231 cells. Apoptotic-like morphological characteristics, along with the downregulation of the expression level of Bcl-2 and Bcl-xL and the upregulation of the expression level of Bad, were observed in Helle-treated MCF-7 cells. Helle also caused the activation of caspase-8, caspase-9, along with the cleavage of poly(ADP-ribose) polymerase in MCF-7 cells. Helle-mediated necrosis-like phenotype, as evidenced by the increased propidium iodide (PI)-positive cells was further observed. G2/M cell cycle arrest was also induced by Helle in the cells. Upregulation of the expression level of p21 and downregulation of the expression level of cyclin D1, cyclin E1, cdc25C and survivin were observed in MCF-7 cells treated with Helle and occurred in parallel with G2/M arrest. Autophagy was triggered in MCF-7 cells and the addition of wortmannin or 3-MA, two well-known autophagy inhibitors, slightly but significantly rescued the cells. Furthermore, similar alterations of some key molecules associated with the aforementioned biological phenomena were observed in MDA-MB-231 cells. Intriguingly, the numbers of PI-positive cells in Helle-treated MCF-7 cells were significantly reduced by wortmannin and 3-MA, respectively. In addition, Helle-triggered G2/M arrest was significantly corrected by wortmannin, suggesting autophagy induction contributed to Helle-induced cytotoxicity of breast cancer cells by modulating necrosis and cell cycle arrest. Collectively, our results suggested potential usefulness of both Helle and Areno in developing therapeutic strategies to treat patients with different types of breast cancer, especially ER-positive breast cancer.